EFFECT OF COCAMIDOPROPYL BETAINE (CAPB) CONCENTRATION ON PHYSICAL CHARACTERISTIC OF BASIL LEAVES (Ocimum basilicum L.) ESSENTIAL OIL FACIAL - Vania Santika Putri; Verawati Hadi; Anita Dwi Nuryani; Ayu Ambarwati (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Atopic dermatitis or often called eczema is a chronic inflammatory skin disorder that often occurs around the face, legs and arms. Decreased skin barrier function can increase the spread of bacteria on the skin surface, especially Staphylococcus aureus. This study aimed to formulate facial wash preparations of basil leaf essential oil using varying concentrations of cocamydopropyl betaine (CAPB) as a surfactant and foam booster. The basil leaf essential oil facial wash was formulated into three formulas with varying concentrations of cocamydopropyl betaine (CAPB), namely F1 (8%), F2 (9%), and F3 (10%). Physical evaluation included organoleptic observations, homogeneity, pH, foam height, and viscosity. Based on the results of organoleptic and homogeneity evaluations, the three facial wash formulas are homogeneous, white in color, and have a distinctive basil smell, with an increasingly watery consistency from F1 to F3, while the pH in the range 4.97 - 5.26, the height foam test of the three formulas was 37–42 mm, and the viscosity was in the range of 2647,1 - 3516,5 cPs. Variations in the CAPB concentration used in the facial wash formulas have a significant effect on the resulting pH and viscosity values, where the higher the CAPB concentration used, the lower pH and viscosity values of the facial wash. However, an increase in CAPB concentration in the facial wash formula (8 %, 9 %, and 10 %) did not have a significant effect on the foam height of the basil leaf essential oil facial wash.